DEVELOPMENT HOTS-ORIENTED MS WORD 2019 PRACTICE QUESTIONS ON THE OFFICE AUTOMATION APPLICATION COURSE - Soraya Fatmawati; Oktavia Hardiyantari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper develops MS Word 2019 practice questions oriented with the HOTS (Higher Order Thinking Skills) on the Office Automation application course. This development research uses the limited ADDIE model, namely Analysis, Design, and Development. The analysis is carried out by identifying problems in the Office Automation application course. Subsequently, the developmental planning of the instrument is carried out. The HOTS-oriented practice questions contain questions in the form of descriptions using indicators of critical thinking, creative thinking, and problem-solving. The data are collected from the assessment of two validation experts using expert validation assessment sheets and responses from 24 students through questionnaires. Data analysis used quantitative descriptive analysis techniques. The research results imply that the HOTS-oriented MS Word 2019 practice questions are feasible to use as teaching materials in the Office Automation application course. It is based on the material expert's assessment was 85.6 with a very feasible category and the result of students’ responses was 83.3 with a very feasible category. The assessment aspects of expert validation include aspects of the relationship between the questions and the material, aspects of the question depth with learning outcomes, and aspects of language.